2000
DOI: 10.1093/alcalc/35.1.60
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Substance Use Between Female Inmates and Female Substance Misusers in Treatment

Abstract: Recent literature documents extensive substance misuse histories among US female prison inmates. The primary purpose of the present study was to determine whether histories of personal and familial substance misuse distinguished female inmates from substance misusers in treatment. After accounting for drug-related offences, we hypothesized that the inmates would have more extensive histories of personal and familial substance misuse and that they would have initiated substance use at an earlier age. Contrary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…51,52 Although therapy is available, there are considerable contraindications, side effects, complex administration schedules, and incomplete efficacy. Finally, numerous studies argue for drug abuse treatment [53][54][55] ; currently, drug-free programs have been the norm in the U.S., and efforts to offer methadone in the correctional setting have been limited. 56,57 Improving access to methadone maintenance in corrections settings is warranted.…”
Section: Entry and During Incarceration: Prevention Of Infection Tranmentioning
confidence: 99%
“…51,52 Although therapy is available, there are considerable contraindications, side effects, complex administration schedules, and incomplete efficacy. Finally, numerous studies argue for drug abuse treatment [53][54][55] ; currently, drug-free programs have been the norm in the U.S., and efforts to offer methadone in the correctional setting have been limited. 56,57 Improving access to methadone maintenance in corrections settings is warranted.…”
Section: Entry and During Incarceration: Prevention Of Infection Tranmentioning
confidence: 99%
“…For example, a comparison between incarcerated women and women who misuse substances and who are in treatment exhibited no group differences in their prevalence of drug and alcohol use, types of illicit substances used, and overall alcohol consumption levels. In fact, incarcerated women actually reported fewer consequences (e.g., medical, legal, psychosocial problems) related to their alcohol use compared to non-incarcerated women in treatment (Phillips et al, 2000). Overall, Phillips and colleagues (2000) concluded that incarcerated women may be quite similar to non-incarcerated, treatment-seeking women (with the exception of their first intoxication, which occurred at a younger age for the incarcerated sample).…”
Section: Substance Abusementioning
confidence: 99%
“…] such that these individuals are in more situations in which crime-related events are likely to occur" (Salgado et al, 2007, p. 21). Also, incarcerated women report an earlier onset of substance use relative to non-incarcerated populations (Phillips, Nixon, Phillips, Pfefferbaum, & Briody, 2000), perhaps explained, in part, by their often chaotic and abusive childhoods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, prior studies have indicated that the use of methamphetamine, a non-opiate synthetic drug, may increase the likelihood of its users engaging in criminal behaviors, including assault, kidnapping, reckless driving, robbery, and homicide [ 22 , 23 ]. Empirical data suggest a strong association between young people’s drug use and criminality, even when dealing in drug and trafficking are disregarded [ 24 , 25 , 26 ]. On the whole, young drug users have been found to be increasingly involved in criminal justice-related issues [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%